The evaluation of the effect of impacted maxillary canine treatment on apical root resorption of maxillary central incisor - Tülin Uğur Taner; Semra Ciğer; Ela Akça (Galenos Yayinevi, 1998)
The aim of this study is to investigate the effect of orthodontic treatment of palatally impacted canines on apical root resorption of maxillary incisor teeth. The sample included 15 subjects who had palatally impacted canine teeth and treated non-extraction with edgewise mechanics and the other 15 subjects treated non-extraction with edgewise mechanics. On the lateral cephalometric headfilms of these patients taken at the beginning and at the end of the treatment, the amount of root resorption was determined by measuring the length of the central incisor teeth. In addition a number of angular and linear measurements were made to determine the labial inclination of the canine and its distance to the occlusal plane. The mean amount of root resorption was found as 1.69±1.68 mm for the impacted canine group while it was measured 0.87±1.01 mm in the other group. The difference between the two groups was not found to be statistically significant. No correlation was found between the amount root resorption and the vertical eruption of the canine tooth. Although the treatment time was longer in the impacted canine group, it was not found to be correlated with the amount root resorption.